Pendidikan Kewirausahaan Berbasis Manajemen Strategik Untuk Kemandirian Ekonomi Santri - Febrianto, Febi; Mohammad Firmansyah; Moh. Rofik; Rausyan Fikri; Aminullah; Muhammad Durrin Ni’am; Mohammad Abdul Aziz Alwahedi; Syaiful Anam (Yayasan Literasi Altruis Khatulistiwa, 2026)
This study aims to explore entrepreneurship education based on strategic management at Al-Mashduqiah Islamic Boarding School in Patokan Probolinggo, focusing on the development of the students' economic independence. The study not only examines the managerial aspects but also uncovers pedagogical dimensions, such as the entrepreneurial learning process, the role of educators, and the learning outcomes experienced by the students. A qualitative case study approach was employed, involving key education subjects: students, educators, and the managers of the pesantren’s business units. Data were collected through in-depth interviews, observations of entrepreneurial activities, and documentation, to analyze the educational interactions between educators and learners in the context of experiential learning. The findings indicate that entrepreneurship education at the pesantren does not only focus on economic skills but also plays a role in developing entrepreneurial competencies in students, making them independent and responsible. This education successfully brings about educational transformation in students, enhancing their ability to manage businesses and understand the management principles applied within the context of pesantren education